Concurrent uveitis in monozygotic twins in the context of systemic sarcoidosis - Doaa Maamoun Ashour; Reem Mohsen; Rahma A. Elziaty; Omnia Bahaa Attia; Haytham Samy Diab; Caroline Atef Tawfik (Journal of Ophthalmic Inflammation and Infection)
Abstract Purpose To report a case of two monozygotic twins presenting with simultaneous onset of bilateral uveitis of variable phenotypic presentations, one of whom was pathologically confirmed to have sarcoidosis. Observation Two 21-year-old monozygotic male twins (Twin A and Twin B) presented with bilateral red eyes and photophobia of six weeks’ duration. Their past medical history included learning difficulties and low IQ since early childhood. Twin A was operated for Celiac Artery Compression Syndrome. Examination and work-up revealed that Twin A had bilateral anterior granulomatous uveitis, and retinal phlebitis in addition to hilar and mediastinal lymphadenopathy. A biopsy was taken, and histopathological examination showed non-caseating granuloma. Twin B had bilateral non-granulomatous anterior uveitis, chorioretinal lesions, and peripheral retinal vasculitis. Genetic testing in the form of a Whole Exome Sequencing was done, and no causal variant was detected for uveitis or sarcoidosis, however, a homozygous likely pathogenic duplication in SYNGAP1 was detected. This mutation is associated with autosomal dominant intellectual developmental disorder. Conclusion This is the first-reported case of concurrent bilateral uveitis in monozygotic twins, with confirmed sarcoidosis in one. This presentation highlights the role of genetic predisposition and shared environmental factors in disease onset and clinical manifestations. Further research into the genetic-environmental interplay is needed to elucidate the mechanisms underlying simultaneous disease onset and guide personalized monitoring strategies for at-risk families.